Analysis of Fiqh Textbooks at Madrasah Tsanawiyah Class VII The Tasamuh Approach in the Perspective of Fiqh Wahbah Musthofa Al-Zuhaili: Analisis Buku Ajar Fikih Madrasah Tsanawiyah Kelas VII Pendekatan Tasamuh dalam Perspektif Fikih Wahbah Musthofa Al-Zuhaili - Ma'arif, Syamsul; Hadi, Muhammad Fazlurrahman (Universitas Muhammadiyah Sidoarjo, 2021)
This research is motivated by the increasing fanaticism of the Fiqh school among students, and it's still found that fiqh books are too exclusive to discuss one particular school, without explaining the meaning of other schools. From this background, several questions arise, including what the attitude of tolerance in the Fiqh textbooks for class VII MTs? What is the concept of tolerance in the Tasamuh approach from the perspective of Fiqh Wahbah Musthofa al-Zuhaili? And what is the relevance of the tolerance attitude of Tasamuh's approach in the perspective of Fiqh Wahbah Musthofa al-Zuhaili in the seventh-grade Islamic Jurisprudence textbook? The purpose of this research is to be a reference for the government and other academics on how fiqh textbooks become more inclusive of differences. This type of research uses a literature study with a qualitative descriptive research approach, while the method of analysis is in the form of content analysis. From this research, it can be concluded: First, that not all Wasatiyah Islamic values are explained in Fiqh textbooks. Second, this part of the Fiqh textbook has accommodated different understandings of Islam well. However, it turns out that many parts of the textbook present one interpretation without including a different interpretation. Third, from several research results that researchers have examined that there is a link between intolerance that occurs in Indonesia and the concept of tolerance in textbooks. The researcher also found that most PAI and Tsanawiyah teachers stated that the Fiqh textbooks used in schools did not contain differences and tended to contain only one understanding of Islamic groups.